ADAM SMITH’S PLURALISM AND THE SCIENCE OF THE LEGISLATOR - Sturn, Richard (Investigación Económica, 2024)
ABSTRACT It is well established that we can make sense of Adam Smith’s multi-faceted account of human agency without incurring “das Adam Smith-Problem”. However, the relevance of his view of knowledge and agency for political economy as science of the legislator deserves to be studied more carefully. Smith’s view of human agency is linked to political realism and pragmatic pluralism, emphasizing the benefits of the knowledge made available by scientific “systems”, but also their limitations and incompleteness. Smith’s Theory of Moral Sentiments, seen together with his realist discussions of mercantilist politics are suggesting explanatory and pragmatic advantages of such pluralism, while opening up horizons of problem-responsive second-best reforms avoiding fallacies of “the man of system”. EL PLURALISMO DE ADAM SMITH Y LA CIENCIA DEL LEGISLADOR RESUMEN Está bien establecido que podemos entender la explicación multifacética de Adam Smith sobre la agencia humana sin incurrir en el “problema de Adam Smith”. Sin embargo, la relevancia de su visión del conocimiento y la agencia para la economía política como ciencia del legislador merece ser estudiada con más cuidado. La visión de Smith sobre la agencia humana está vinculada al realismo político y al pluralismo pragmático, enfatizando los beneficios del conocimiento que brindan los “sistemas” científicos, pero también sus limitaciones e incompletitud. La teoría de los sentimientos morales de Smith, vista junto con sus discusiones realistas sobre la política mercantilista, sugiere ventajas explicativas y pragmáticas de dicho pluralismo, al tiempo que abre horizontes de reformas de segunda opción que responden a los problemas y evitan las falacias del “hombre del sistema”.